2021
DOI: 10.1101/2021.12.04.471085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical Face-Selective Responses Emerge Early in Human Infancy

Abstract: Faces are a rich source of social information. How does the infant brain develop the ability to recognize faces and identify potential social partners? We collected functional magnetic neuroimaging (fMRI) data from 49 awake human infants (aged 2.5-9.7 months) while they watched movies of faces, bodies, objects, and scenes. Face-selective responses were observed not only in ventral temporal cortex (VTC) but also in superior temporal sulcus (STS), and medial prefrontal cortex (MPFC). Face responses were also obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 261 publications
2
3
0
Order By: Relevance
“…In particular, recent literature confirmed crucial effective connectivity among these areas, thus confirming the connections described by models of the core system of face perception [25]. Furthermore, most recent advances in the literature confirmed the specialization of the areas involved in this system [92]. According to our results, the facial information processing appears to stop at the FFG stage for faces that generate a sympathetic response, since forward connections towards the MTG are inhibited while backward connections to the FFG are enhanced.…”
Section: Discussionsupporting
confidence: 73%
“…In particular, recent literature confirmed crucial effective connectivity among these areas, thus confirming the connections described by models of the core system of face perception [25]. Furthermore, most recent advances in the literature confirmed the specialization of the areas involved in this system [92]. According to our results, the facial information processing appears to stop at the FFG stage for faces that generate a sympathetic response, since forward connections towards the MTG are inhibited while backward connections to the FFG are enhanced.…”
Section: Discussionsupporting
confidence: 73%
“…Given those findings, it could have been thought that face circuitry (including face identification and articulatory movement perception) would have been fully in place prior to reading acquisition. However, many findings, including the present ones, conclusively show that the development of face responsivity in the fusiform gyrus is protracted: fMRI responses selective to faces are detectable in infants (Tzourio-Mazoyer et al, 2002; Deen et al, 2017; Kosakowski et al, 2021) and pre-schoolers (Cantlon et al, 2011), but they continue to develop with age throughout childhood and into adolescence (Golarai et al, 2007; Scherf et al, 2007; Grill-Spector et al, 2008; Peelen et al, 2009).…”
Section: Discussionsupporting
confidence: 59%
“…The spatial organization of category-specific responses is known to develop slowly during childhood and even adolescence. In infants, a rough medial-to-lateral partition is already observed during the first year of life, with medial responses to places and lateral responses to faces and tools, yet the activations to faces were initially reported to be indistinguishable from those to tools (Deen et al, 2017), but with improved MRI method, a recent study reported activation selective to faces relative to objects in infancy (Kosakowski et al, 2021). Later in childhood, we and others found that fusiform face responses are clearly present, for instance in kindergartners (Cantlon, Pinel, Dehaene, & Pelphrey, 2011; Dehaene-Lambertz et al, 2018), but continue to slowly grow until adolescence (Golarai et al, 2007; Scherf, Behrmann, Humphreys, & Luna, 2007; Grill-Spector, Golarai, & Gabrieli, 2008; Peelen, Glaser, Vuilleumier, & Eliez, 2009; Natu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Data were cleaved between consecutive timepoints having more than 2 degrees or 2 mm of frame-toframe displacement, creating subruns, each of which contained at least 48 consecutive low-motion (less than 2 degrees/mm of motion) volumes. These motion exclusion criteria are similar to previously reported thresholds [91][92][93]. All volumes included in a subrun were extracted from the original run data and combined to create a new Nifti file for each subrun.…”
Section: Scanning Sessionmentioning
confidence: 99%
“…Within each subrun, volumes with greater than 0.5 degrees/mm of motion between volumes were scrubbed. As in our previous research, if more than 3 consecutive images were scrubbed, there had to be at least 7 consecutive low-motion volumes following the scrubbed volume in order for those volumes to be included in the analysis [91,92]. Each subrun had to have at least 48 volumes after accounting for motion.…”
Section: Scanning Sessionmentioning
confidence: 99%